Social Integration of the Dayak Kanayatn Community Through the Balale' Uma Tradition in Tonang Village, Landak Regency - Sulastri, Genovepa Dede; Bahari, Yohanes; Imanulyaqin, Muhammad Nur; Imran, Imran; Utami, Patrisia Rahayu; Pattisinai, Amanda Ristriana (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
This study describes the role of the Balale' Uma tradition in the social integration of the Dayak Kanayatn community in Tonang Village, Landak Regency, West Kalimantan, Indonesia. As a traditional form of collective farming, Balale' Uma embodies solidarity, shared goals, and camaraderie among a multicultural community. Using a descriptive method with a qualitative approach, data were collected through observation and in-depth interviews with community leaders, traditional authorities, and local residents. Informants in the study included Tuha Tahutn, the Chairman of Ale’an, members of the Balale' Uma community, and the general public. The research findings indicate that the practice of Balale’ Uma not only supports agricultural activities but also serves as a medium for interfaith unity and harmony among diverse groups, thereby strengthening social integration despite the challenges of modernization. This study highlights the importance of customary traditions in preserving cultural sustainability and reinforcing community resilience, while offering broader insights into how local practices contribute to social integration within a diverse society. The research method employed a qualitative approach with a descriptive focus to describe the phenomena observed, such as the social integration occurring in Tonang Village, Landak Regency, through the Balale’ Uma tradition. The findings of this study indicate that social integration through the balale’ uma tradition remains intact, despite being slightly influenced by the influx of modernization, such as the introduction of tractors in rice field cultivation. However, social integration continues in the process of planting and harvesting rice.